Digital training for increasing English teachers’ professionalism at junior high school - Syafryadin Syafryadin; Dian Eka Chandra Wardhana; R.Bunga Febriani (Intelektual Pustaka Media Utama, 2021)
This research aimed to know the problems and the implementation of the training as the solution and evaluation of digital training that can increase the English teachers’ professionalism at SMP Negeri 13 Bengkulu, Indonesia. This study used a descriptive qualitative method with the number of trainees were 10 English teachers. The procedures of collecting data were observation, documentation and interview. Then, the data analysis were done by comparing the result of the interview from the English teachers at SMP Negeri 13 Bengkulu, Indonesia before they joined and after joining digital training provided by the researchers and finally concluded. The first research finding is the English teachers had problems in terms of knowledge, difficult to apply the application or technology, and never joining training. The second finding is the implementation of digital training had many benefits namely increased the English teachers’ professionalism, experienced and innovated their knowledge and skills toward the use of digital learning, it brought a good quality for learning outcomes and it helped to be better in an advanced educational institution, particularly at SMP Negeri 13 Bengkulu, Indonesia. The last finding is that after implementation, the English teachers still got problems in using the application and need more training. The implication of this study is digital training can be an advanced way in educational development which needs good participation from the trainers, trainees and educational institution.